PENJATUHAN KEBIRI KIMIA BAGI PELAKU KEKERASAN SEKSUAL DALAM PANDANGAN HAK ASASI MANUSIA - S, Zulkarnain; Asra Rahmad, Riadi (Desiderata Law Review, 2024)
Abstract The aim of this research is, firstly, the regulation of chemical castration for perpetrators of sexual violence, secondly, how chemical castration is for perpetrators of sexual violence from a human rights perspective. The research method in this article is normative juridical research. Government Regulation no. 70 of 2020 was prepared to complete an in-depth discussion regarding chemical castration, because the previous regulation, namely Government Regulation in Lieu of Law no. 1 of 2016 which was later enacted into Law no. 17 of 2016 only briefly discusses the punishment of chemical castration, as intended in Article 81 paragraph 7. Human Rights (HAM) are rights that are inherent in humans and cannot be removed or abolished, and these rights must be respected, protected and upheld by the state, government and all people in the world. Human Rights (HAM) are contained in Law Number 39 of 1999 concerning Human Rights. The act of chemical castration in Law Number 17 of 2016 which is intended for perpetrators of sexual violence against children for a period of 2 (two) years, seen from a Human Rights (HAM) perspective, is considered to violate Article 33 of Law Number 39 of 1999 concerning Rights. Human Rights (HAM) which states that everyone has the right to be free from torturous punishment. Abstrak Adapun tujuan dari penelitian ini adalah yang pertama pengaturan mengenai pidana kebiri kimia bagi pelaku kekerasan seksual, yang kedua bagaimana kebiri kimia bagi pelaku kekerasan seksual dalam pandangan Hak Asasi Manusia. Metode penelitian dalam artikel ini adalah penelitian yuridis normatif. Peraturan Pemerintah No. 70 Tahun 2020 disusun untuk melengkapi pembahasan secara mendalam terkait kebiri kimia, karena pada peraturan sebelumnya yakni Peraturan Pemerintah Pengganti Undang-undang No. 1 Tahun 2016 yang kemudian ditetapkan menjadi Undang-undang No. 17 Tahun 2016 hanya membahas sekilas tentang hukuman kebiri kimia, sebagaimana yang dimaksud dalam Pasal 81 ayat 7. Hak Asasi Manusia (HAM) merupakan hak yang melekat pada mausia dan tidak dapat untuk dihilangkan maupun dihapuskan yang mana hak tersebut wajib untuk dihormati, dilindungi, dan dijunjung tinggi oleh Negara, pemerintah, dan seluruh manusia di dunia. Hak Asasi Manusia (HAM) tertuang di dalam Undang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia. Tindakan kebiri kimia di dalam Undang-Undang Nomor 17 Tahun 2016 yang diperuntukkan bagi pelaku kekerasan seksual terhadap anak selama jangka waktu 2 (dua) tahun dilihat dari perspektif Hak Asasi Manusia (HAM) dianggap melanggar Pasal 33 Undang- Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia (HAM) yang menyatakan bahwa setiap orang berhak untuk bebas dari hukuman yang menyiksa.